2011
DOI: 10.1590/s0365-05962011000700037
|View full text |Cite
|
Sign up to set email alerts
|

Psoríase eritrodérmica com regressão após profilaxia com isoniazida e terapia antidepressiva: relato de caso

Abstract: An 83 year old woman, exhibiting severe psoriasis, was treated conventionally (phototherapy, acitretin, and cyclosporine). After poor clinical results and significant changes in laboratory procedures, those treatments were suspended. She was then being prepared to be submitted to biological treatment, when preliminary results disclosed a 30mm PPD. Complete improvement occurred [only] after introducing prophylactic therapy for tuberculosis and anti-depressive medication. Keywords: Acitretin; Antidepressive agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…In fact in two studies done by Gupta et al [18,19], an increase in stress and depressive symptoms were found to have a significant statistical correlation with an increase in psoriasis flare-ups and pruritus severity along with a more clinically disfiguring disease. In addition, studies have shown that a decrease in depression/depressive symptoms due to medication or therapy is associated with a decrease in psoriasis severity and vice versa [20,21,22,23,24,25,26]. The question now remains: is this correlation merely due to the negative psychological effects inherent in any clearly discernible skin disorder, or any disorder in general, such as social anxiety, low self-esteem, shame/embarrassment etc., or is there an underlying pathophysiological mechanism involved?…”
Section: Depression and Psoriasis: A Psychodermatological Associationmentioning
confidence: 99%
“…In fact in two studies done by Gupta et al [18,19], an increase in stress and depressive symptoms were found to have a significant statistical correlation with an increase in psoriasis flare-ups and pruritus severity along with a more clinically disfiguring disease. In addition, studies have shown that a decrease in depression/depressive symptoms due to medication or therapy is associated with a decrease in psoriasis severity and vice versa [20,21,22,23,24,25,26]. The question now remains: is this correlation merely due to the negative psychological effects inherent in any clearly discernible skin disorder, or any disorder in general, such as social anxiety, low self-esteem, shame/embarrassment etc., or is there an underlying pathophysiological mechanism involved?…”
Section: Depression and Psoriasis: A Psychodermatological Associationmentioning
confidence: 99%
“…Psoriasis patients have an increased risk of depression, anxiety and suicidality compared to the general population 77–80 . Numerous studies have demonstrated a correlation between psoriasis and MDD 81–90 . Antidepressant treatment and phototherapy have been found to reduce psoriatic clinical morbidity and also depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80] Numerous studies have demonstrated a correlation between psoriasis and MDD. [81][82][83][84][85][86][87][88][89][90] Antidepressant treatment and phototherapy have been found to reduce psoriatic clinical morbidity and also depressive symptoms. Consequently, there is the possibility that MC1R may have a role in predisposition to psoriasis and depression through the hypothalamic pituitary adrenal axis responses to immune regulation and to stress.…”
Section: F I G U R Ementioning
confidence: 99%
“…9 No caso relatado, seguiu-se o protocolo terapêutico de psoríase do Ministério da Saúde. A eliminação dos prováveis fatores desencadeantes é passo essencial e preliminar na abordagem terapêutica, 5 o que justifica a referência do paciente deste caso ao NASF, para que fosse cuidado e assistido pela equipe multidisciplinar, em especial pelo psicólogo, tendo em vista o desequilíbrio emocional em que se encontrava, minimizando os danos psicossociais que a doença provocou.…”
Section: Discussionunclassified
“…2,3,4 As infecções bacterianas, os medicamentos e o estresse emocional estão entre os fatores desencadeantes da psoríase, que compromete a pele, os anexos cutâneos e as articulações, atingindo aproximadamente 2% da população mundial e acarretando significativos danos psicossociais. 5,6,7 Objetiva-se, neste artigo, relatar um caso clínico de HPI, surgida após um quadro de psoríase, cujo diagnóstico e tratamento coube aos profissionais da RAS do município de Vassouras, na região Centro Sul Fluminense. Na anamnese, relatou ao médico que há cerca de 10 anos, surgiram as primeiras manchas descamativas ao longo do seu corpo, mais precisamente na região de membros inferiores, que aumentaram gradativamente de tamanho, com o decorrer dos meses, e estenderam-se para outras partes, como antebraço direito e tronco.…”
Section: Introductionunclassified